Effects of two problem solving methods on senior secondary school students’ performance in simultaneous equations in Ekiti State - Ojo, Oluwatoyin Faith (Advances in Social Sciences Research Journal, 2019)
Abstract The study investigated the Effects of two Problem Solving Methods on Senior Secondary School Students’ performance in Simultaneous Equations in Ekiti State. The study employed quasi experimental pre-test post-test, control group design. The sample consisted of 302 senior secondary school II students. Multistage sampling procedures were used to select the sample. The instrument used for the study was a test format tagged "Mathematics Performance test (MPT)".The face and content validity of the instrument was ascertained while test retest method was used to ensure the reliability which yielded reliability coefficient of 0.71. Data collected were analysed descriptively using mean, standard deviation for the research question, Analysis of Variance (ANOVA) and Analysis of Covariance (ANCOVA) were used for hypotheses one and two respectively both at 0.05 level of significance. The findings revealed that, the use of KPS and PPS enhanced better performance of senior secondary school students in simultaneous equations than the CM. KPS was most effective for enhancing better students’ performance in simultaneous equations, followed by PPS method and lastly conventional method. It was therefore recommended that the use of KPS and PPS methods should be encouraged in Mathematics to enhance better performance of students in simultaneous equations. Also, Mathematics teachers should be given adequate orientation through workshops and seminars to update their knowledge in the use of KPS and PPS methods in teaching. Keywords: Problem Solving Methods, Kolawole’s Problem Solving (KPS) method, Polya’s Problem Solving (PPS) method, Conventional method, performance, Simultaneous Equations